Test battery for the evaluation and assessment of movement abilities in elite Polish wrestlers - Starosta, W.; Rynkiewicz, T. (International Journal of Wrestling Science, 2014)
The process of sport training requires rational development of movement abilities, as well as the technical and tactical skills of the athletes. An improvement in its effectiveness necessitates not only the application of appropriate loads, but also the control of the scope and direction of the occurring changes. In order to provide an evaluation of the effectiveness of the training process and the level of movement abilities in advanced wrestlers, our aim was to seek an optimal set of tests for this purpose. To eliminate the effects of body weight, results are expressed in units relative to body weight. The subjects were 45 wrestlers aged 15-20, with an average training experience of 6.6 years, and a national ranking. A wide range of tests was applied to carry out an evaluation of general and special physical and co-ordination movement abilities (5). The following tests were performed: maximum rotation in a jump, zigzag run, run with forward roll, pull up, dips from support on parallel bars, bench presses, clean and jerk, twisting bends of the torso, barbell cleans, squats with barbell, vertical jump, a 20m run, a 1500m run, bending of the trunk backwards, forward throw, backward throw, backward somersault, forward somersault, "scrambling", "bridging", "pressing from shoulders" and "bridging passes". Results. With the use of the method in which features are grouped, they were divided into several groups characterised by high mutual similarity. It was decided that of prime importance were physical, general and special coordination abilities. Test results which showed the smallest similarity were also determined. Among them were: speed values in 20m and 1500m runs, results of tests of global movement coordination and basic body build indices. Conclusions. An analysis of correlation indices was applied and a reduction of multiple regression was made to select the optimal set of tests for evaluation of general and special preparation of wrestlers. Furthermore, tests were include based on a compromise between supplying sufficient range of information, while avoiding interference with the training process.